Pendidikan Lingkungan pada Mata Kuliah Pendukung Pemanfaatan Kebun Percobaan di Jurusan Biologi - Arsal, Andi Faridah; Dirawan, Gufron D; Hala, Yusminah; Tahmir, Suradi (UNM Environmental Journals, 2018)
This study aims: (1). To identify the main support system in the design of environment-based learning in the Department of Biology, Faculty of Mathematics and Natural Sciences, Makassar State University. (2). Knowing the use of environment-based learning resources in the Department of Biology, Faculty of Mathematics and Natural Sciences, Makassar State University. Through the Needs Assessment instrument in the form of field observations, questionnaire surveys, and interviews with lecturers and students identified problems to determine the right action for the next stage, so the design of learning to be carried out is the best solution. The results of the study are that (1). The Biology Department of UNM has two main locations or areas that strongly support environment-based learning with their respective characteristics. The two areas are the Biology Experiment Garden and the Field of Library Discussion of the Biology Department of FMIPA UNM. (2) Some courses have made use of environment-based learning resources in the Biology Department of FMIPA UNM. Solutions from the identification results obtained are among others; (1). The Department of Biology can be used as a place of learning, a source of learning, and as a learning media in the design of environment-based learning. (2). The Biology Department can be used as a comfortable and pleasant learning environment for the entire academic community. (3). The design of Environmental Based Learning in the Biology Department of UNM can be done in almost all subjects by increasing the role of the lecturer as a facilitator.